Collagen Nanoparticle-Mediated Brain Silymarin Delivery: An Approach for Treating Cerebral Ischemia and Reperfusion-Induced Brain Injury - Rathore, Pankaj; Arora, Indu; Rastogi, Shweta; Akhtar, Mohd; Singh, Shruti; Samim, Mohammed (Frontiers in Neuroscience, 2020)
Silymarin is a bioactive constituent isolated from milk thistle (Silybum marinum). Since its discovery, silymarin has been considered a gold standard drug in treating ailments related to the liver, resulting from alcohol consumption and viral hepatitis. This hepatoprotective nature of silymarin arises out of antioxidative and tissue-regenerating properties of silymarin. However, several recent studies have established the neuroprotective link of silymarin, too. Thus, the current investigation was aimed at exploring the neuroprotective effect of nanosilymarin (silymarin encapsulated inside collagen-based polymeric nanoparticulate drug delivery system). The study aimed at bringing out the role of nanoparticles in enhancing the therapeutic effect of silymarin against neuronal injury, originating out of oxidative-stress-related brain damages in focal cerebral ischemia. Collagen-based micellar nanoparticles were prepared and stabilized using 3-ethyl carbodiimide-hydrochloride (EDC-Hcl) and malondialdehyde (MDA) as crosslinkers. Nanoparticles were characterized using dynamic light scattering (DLS), transmission electron microscopy (TEM), and Fourier transform infrared (FT-IR) spectroscopy techniques, and the size of nanoparticles was found to be around 48 nm. Male albino Wistar rats were pretreated with three different doses of nanosilymarin of 10, 100, and 1,000 μg/kg b.wt and a dose of free silymarin of 100 mg/kg b.wt intraperitoneally (i.p.) for 7 days. Focal cerebral ischemia was induced using the middle cerebral artery occlusion (MCAO) model on the eighth day for 1 h followed by 24 h reperfusion. The animals were then evaluated for neurobehavioral, infarct analysis, biochemical, histopathological, and immunohistochemical studies. All the above parameters showed remarkable improvement in nanosilymarin-treated groups in comparison to the silymarin-treated group. Nanoparticle encapsulation of drug enhanced neuroprotection by increasing drug bioavailability and targeting. Thus, the present study concluded with satisfactory results, showing the critical role played by nanoparticles in improving the neuroprotection at very low drug doses.